NLRP3 Inflammasome Mediates Dormant Neutrophil Recruitment following Sterile Lung Injury and Protects against Subsequent Bacterial Pneumonia in Mice - Tian, Xiaoli; Sun, He; Casbon, Amy-Jo; Lim, Edward; Francis, Kevin P.; Hellman, Judith; Prakash, Arun (Frontiers in Immunology, 2017)
Sterile lung injury is an important clinical problem that complicates the course of severely ill patients. Interruption of blood flow, namely ischemia-reperfusion (IR), initiates a sterile inflammatory response in the lung that is believed to be maladaptive. The rationale for this study was to elucidate the molecular basis for lung IR inflammation and whether it is maladaptive or beneficial. Using a mouse model of lung IR, we demonstrate that sequential blocking of inflammasomes (specifically, NLRP3), inflammatory caspases, and IL-1β, all resulted in an attenuated inflammatory response. IL-1β production appeared to predominantly originate in conjunction with alveolar type II epithelial cells (AT2). Lung IR injury recruited unactivated or dormant neutrophils producing less reactive oxygen species thereby challenging the notion that recruited neutrophils are terminally activated. However, lung IR inflammation was able to limit or reduce the bacterial burden from subsequent experimentally-induced pneumonia. Notably, inflammasome-deficient mice were unable to alter this bacterial burden following IR. Thus, we conclude that the NLRP3 inflammasome, through IL-1β production, regulates lung IR inflammation, which includes recruitment of dormant neutrophils. The sterile IR inflammatory response appears to serve an important function in inducing resistance to subsequent bacterial pneumonia and may constitute a critical part of early host responses to infection in trauma.